Management Would Be Easy...If It Weren't for the People - Addesso, Patricia J (New York AMACOM, 1996)
A guide to managing people more effectively by understanding the basic principles of psychology. In this ready-when-you-need-it guidebook, managers learn the basics of psychology--what makes people tick. Armed with this knowledge, they can influence behavior appropriately.
Age Group: Adult
Includes bibliographical references (p. 177-179) and index.
Keywords: Personnel Management; Psychology, Industrial